2015
DOI: 10.1146/annurev-arplant-043014-114700
|View full text |Cite
|
Sign up to set email alerts
|

United in Diversity: Mechanosensitive Ion Channels in Plants

Abstract: Mechanosensitive (MS) ion channels are a common mechanism for perceiving and responding to mechanical force. This class of mechanoreceptors is capable of transducing membrane tension directly into ion flux. In plant systems, MS ion channels have been proposed to play a wide array of roles, from the perception of touch and gravity to the osmotic homeostasis of intracellular organelles. Three families of plant MS ion channels have been identified: the MscS-like (MSL), Mid1-complementing activity (MCA), and two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 137 publications
(223 reference statements)
0
148
0
3
Order By: Relevance
“…We found that the extensive vacuole network of the mutant scolopale cells in the FCO was reduced in size compared to wild-type. Various mechanosensors contribute to maintaining vacuolar structures in cells 47, 48 and growing evidence suggests that TRP channels play critical roles in regulating cell size and shape 49 . This raises the possibility that TRPγ plays a similar role in these support cells, which in turn helps maintain the structural stability of the mechanosensory organs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the extensive vacuole network of the mutant scolopale cells in the FCO was reduced in size compared to wild-type. Various mechanosensors contribute to maintaining vacuolar structures in cells 47, 48 and growing evidence suggests that TRP channels play critical roles in regulating cell size and shape 49 . This raises the possibility that TRPγ plays a similar role in these support cells, which in turn helps maintain the structural stability of the mechanosensory organs.…”
Section: Discussionmentioning
confidence: 99%
“…This influx would then prime the cell for further amplification and propagation. Although Ca 2+ increases are strongly linked to mechanical signaling in plants (for review, see Toyota and Gilroy, 2013), and an array of likely plant mechano-sensitive elements such as OSCA1 (Yuan et al, 2014), receptorlike kinases (Shih et al, 2014), and the MSL, MCA, and TPK channels (for review, see Hamilton et al, 2015) have been identified, the possible roles of such mechanical sensors and channels in rapid systemic signaling have yet to be fully explored.…”
Section: Hydraulic Waves Mechano-sensors and The Calcium Wavementioning
confidence: 99%
“…For example, small mechanosensitive channel-like (MscS-like) Arabidopsis homolog AtMSL3, was shown to rescue the osmotic-shock sensitivity of a bacterial mutant lacking MS-channel activity [91]. Localized in the envelope, AtMSL3 has been shown to control plastid size and shape, to protect plastids from hypo-osmotic stress, and serve as component of the chloroplast division machinery [91].…”
Section: Chloroplastsmentioning
confidence: 99%
“…For example, small mechanosensitive channel-like (MscS-like) Arabidopsis homolog AtMSL3, was shown to rescue the osmotic-shock sensitivity of a bacterial mutant lacking MS-channel activity [91]. Localized in the envelope, AtMSL3 has been shown to control plastid size and shape, to protect plastids from hypo-osmotic stress, and serve as component of the chloroplast division machinery [91]. Two-pore potassium channel TPK3, located in the thylakoid membrane, was shown to be a crucial player in the optimization of photosynthesis, by influencing the proton motive force (see [92] and SI Ref.…”
Section: Chloroplastsmentioning
confidence: 99%